2020
DOI: 10.3390/s20123504
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid SVM-CNN Classification Technique for Human–Vehicle Targets in an Automotive LFMCW Radar

Abstract: Human–vehicle classification is an essential component to avoiding accidents in autonomous driving. The classification technique based on the automotive radar sensor has been paid more attention by related researchers, owing to its robustness to low-light conditions and severe weather. In the paper, we propose a hybrid support vector machine–convolutional neural network (SVM-CNN) approach to address the class-imbalance classification of vehicles and pedestrians with limited experimental radar data available. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…The functionalities of this tier in addition to the database server are depicted in Figure 8: newPro-ductEntry, openBox, sensorAlert, handleProduct, emptyPackageExit, sendToBlockchain, prediction, correlation and patterDetection. A sequence diagram in Figure 9 illustrates interactions between tier 2 functions, along with their relationships with other modules, including the occurrence of events, their blockchains recording, and the activation of desired machine learning functions (i.e., prediction [48], classification [49] and clusterization [50]). Tier 2 has the following security properties: (a) every table has a hash field; (b) there is a shadow table…”
Section: Tier 2-data Processing and Machine Learningmentioning
confidence: 99%
“…The functionalities of this tier in addition to the database server are depicted in Figure 8: newPro-ductEntry, openBox, sensorAlert, handleProduct, emptyPackageExit, sendToBlockchain, prediction, correlation and patterDetection. A sequence diagram in Figure 9 illustrates interactions between tier 2 functions, along with their relationships with other modules, including the occurrence of events, their blockchains recording, and the activation of desired machine learning functions (i.e., prediction [48], classification [49] and clusterization [50]). Tier 2 has the following security properties: (a) every table has a hash field; (b) there is a shadow table…”
Section: Tier 2-data Processing and Machine Learningmentioning
confidence: 99%
“…Some machine learning based research results have been previously reported [42], but with experiments conducted in a very controlled environment where the subjects were stationary. In a related work [43], a deep learning based classification method was used for differentiating a human from a vehicle on road. In this paper, a CNN classifier is used to extract salient features and discriminate the cart from human targets.…”
Section: Introductionmentioning
confidence: 99%
“…For all these actions mentioned above, studies and developments are essential to improve pedestrian detection systems and algorithms, either by using statistical models [ 18 ], combining the use of different detection systems [ 19 ], defining complex scenarios [ 20 ], improving algorithms for tracking detected pedestrians [ 21 , 22 ], developing algorithms for detecting and tracking multiple pedestrians [ 23 , 24 , 25 ], or by using machine learning algorithms [ 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%